The RelationshipBetween Entrepreneurship Education And Mentoring Toward Entrepreneurship Intention - Sabrina O. Sihombing, Elisse Natalia, (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2018)
This study aims to determine the relationship between factors that influence entrepreneurial intentions which consist of entrepreneurship education, entrepreneurial attitudes, subjective norms, self efficacy, and mentoring. Research on factors that influence entrepreneurship has been carried out by many previous researchers. However, mentoring is a variable that is rarely studied in previous studies. This study will discuss more about the variable mentoring. In this study, the quantitative paradigm was used as the basis of this study, with the type of descriptive research. The object of research used is the entrepreneurship study program. While the analysis unit used is an individual. Data collection methods in the form of questionnaires with 24 indicators with an interval measurement scale that is a 5-point Likert scale. The sampling design used is non-probability sampling, namely judgment sampling with students and students majoring in entrepreneurship as active as a sample. The number of samples used in this study is 85 for preliminary studies, and 157 for actual research studies. After the data is collected, the data is then tested for reliability and validity using Cronbach's Alpha and construct validity using Pearson Correlation and also Exploratory Factor Analysis (EFA). After passing the reliability and validity tests, of the 24 indicators used previously, only 15 indicators met the requirements for reliability testing and validity testing. Then the data was then analyzed using PLS-SEM. The results of this study are from eight pre-determined hypotheses, there are two hypotheses that are not supported by several reasons. From this study, it can be concluded that there is no relationship between entrepreneurial education and student self-efficacy, and the absence of a relationship between mentoring and student self-efficacy.